Standardized Nutritional Care with a High-Energy, High-Protein Diet in Rectosigmoid Cancer Patients Undergoing Chemotherapy: Case Reports - Noviyanti Safitri Rahmat; Tri Siswati; Isti Suryani; Siti Budi Utami; Setyowati Setyowati; Nurhidayat Nurhidayat; Susilo Wirawan (Health Dynamics, 2026)
Rectosigmoid cancer patients undergoing chemotherapy are at high risk of malnutrition due to metabolic alterations and treatment-related gastrointestinal side effects. Evidence on the implementation of standardized nutritional care in primary healthcare settings remains limited. This study aims to evaluate the provision of standardized nutritional care with a diet high in energy and protein and its impact on the intake, nutritional status, and clinical condition of rectosigmoid cancer patients undergoing chemotherapy. The case was a 50-year-old male with stage III rectosigmoid cancer undergoing chemotherapy, who presented with undernourished status, diarrhea, reduced appetite, dysphagia-related discomfort, and anemia. Nutritional assessment identified inadequate oral intake and increased energy and protein requirements. Standardized nutritional care was implemented using the Nutrition Care Process (NCP) framework, including an individualized high-energy, high-protein (HEHP) diet and nutrition education for the patient and family. Dietary intake was monitored over three consecutive days using 24-hour food recalls. The patient demonstrated improved tolerance to oral intake, increased protein consumption, stabilization of body weight, and no worsening of gastrointestinal symptoms during the intervention period. This case illustrates that standardized nutritional care using a high-energy, high-protein diet can support dietary intake and help maintain nutritional status in rectosigmoid cancer patients undergoing chemotherapy, even in a primary healthcare setting. Early and individualized nutritional intervention may play an important role in preventing further nutritional deterioration and supporting comprehensive cancer care.